(untitled) (International Congress on Economics, Management and Business Studies, 2026)
The article examines contemporary approaches to improving the practice of financing investment projects through syndicated loans provided by commercial banks. In the context of accelerated economic growth and the implementation of large-scale investment programs, the demand for substantial financial resources continues to increase, often exceeding the lending capacity of individual banks. Under these circumstances, syndicated lending serves as an effective financial instrument for mobilizing capital, enabling the distribution of credit risk among several financial institutions, strengthening the stability of the banking sector, and facilitating the financing of large infrastructure, industrial, and energy projects. The study analyzes the major advantages of syndicated lending, including credit risk diversification, improved bank liquidity, expanded lending capacity, and enhanced interbank cooperation. Particular attention is paid to the current challenges hindering the development of the syndicated loan market in the Republic of Uzbekistan, such as the lack of a harmonized regulatory framework, limited experience in organizing banking syndicates, the absence of standardized loan documentation, and the insufficient digitalization of banking processes.